A Cephalometric Analysis of Hemifacial Microsomia - Xiaoli Li; Zhenghui Wang; Zhuangqun Yang; Min Xu (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2015)
Objective: The purpose of the present study was to analyze the facial asymmetry systematically using the cephalometric method, so as to demonstrate the difference on both sides of Hemifacial microsomia(HFM) in adult. Study Design: Twelve adults of HFM were chosen, and the muscles and velocity of conduction of facial nerve were measured using the electromyographic machine. We collected all the patients' cephalometric radiographs in the anterior and posterior projections and analysed the size and symmetry of orbit, maxilla and mandible.  Results: We found the dysfunction of muscles and facial nerves on the affected side of HFM. The main differences on both sides were the mandible and the changes in the orbit, but the maxilla had no significant difference. Conclusion: The quantitative analysis supports the objective data for clinic and the hard tissues and soft tissues must be considered in order to help with the treatment of HFM.